Prerequisites for Process Management Implementation in the Public Administration of Ukraine - Khadzhyradieva, Svitlana; Docsenko, Tatyana; Sitsinska, Maya; Baiun, Yurii; Pukir, Yuliia (International Journal of Criminology and Sociology, 2021)
The main objective of the study is to analyse the prerequisites for the implementation of process management in public administration of Ukraine. In the process of identifying the presence of certain prerequisites in modern Ukrainian realities, methods of analysis of economic statistics and international indices that determine the level of technological and economic development of the country, as well as readiness to use information and communication technologies have been used. It has been determined that the evolution of management systems is derived from the development of managed objects. Therefore, the development of technologies as a way to transform matter, energy and information is the main determinant of the quality characteristics of management systems. It has been proved that given the global openness of the national economy and in a situation of insufficient technological level, there are opportunities for catch-up development in Ukraine, based on the introduction of digitalization technologies, which are used mainly in the sphere of services – financial, educational, public, etc. As a result, the introduction of information technologies will facilitate the transition to new rules for companies, organizations and government agencies. Taking this into account, there is an urgent opportunity in Ukraine to introduce process management tools and improve the efficiency of public administration and local self-government systems. However, changing the management system, in addition to process modelling and optimization, will require the transformation of cognitive models of civil servants as a sufficient condition for the effectiveness of the implemented system.